Community Service-Learning in a Large Introductory Sociology Course: Reflections on the Instructional Experience (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2018)
This paper reports on a pilot project that involved the incorporation of Community Service-Learning (CSL) into a large Introductory Sociology class by drawing on the critical reflections of the six graduate student instructors and the primary instructor who taught the course. Graduate student instructors individually facilitated weekly seminars for about 30 undergraduate students, half of which participated in CSL, completing 20 hours of volunteer work with a local non-profit community organization. We discuss the benefits of incorporating CSL into a large Introductory Sociology class and speculate on the value of our particular course format for the professional development of graduate student instructors. A main finding was the critical importance to graduate students of formal and informal training and collaboration prior to and during the delivery of the course. Graduate students found useful exposure to CSL as pedagogical theory and practice, and appreciated the hands-on teaching experience. Challenges with this course structure include the difficulty of seamlessly incorporating CSL student experiences into the class, dealing with the “CSL”/ “non CSL” student division, and the nature of some of the CSL placements. We conclude by discussing possible methods for dealing with these challenges.